UJI VARIABEL POTENSI DAN PERTUMBUHAN DARI KOMUNITAS KEPITING WARNA WARNI GENUS FIDDLER (Uca Spp) DI KKMB KOTA TARAKAN - ., Jamiluddin; ., Rizal; ,, Alfrida; Achyani, Ratno (Jurnal Harpodon Borneo, 2013)
Colorful crabs of the genus Uca Spp known by the scientific name of the fiddler. Type genus Fiddler (Uca spp) is one of the endemic biota that has properties Fiddler crabsbecause this life is very dependent on the ecosystem of mangrove forest , one of which is found in mangrove forest ecosystems located KKMB in Tarakan City. The purpose is to know the relationship between the growth allometri length and width of carapace with a total weight of fiddler crabs (Uca sp) ; Knowing the potential of the test proteins from several species of fiddler crabs (Uca sp) ; Knowing the condition of the habitat of fiddler crabs (Uca sp) in KKMB Tarakan city.Research methods using descriptive research method . The scope of this study only focused variables test a protein and morphometry of community genus colorful crabs genus fiddler (Uca spp). The results of the morphometry of the kind Uca Dussumeri , Uca crassipes, Uca Rosea, Uca arcuata, Uca Tetragonon, Uca Vocans to the relationship between carapace length to total weight obtained allometri growth is negative and the relationship between the width of the carapace with a total weight obtained allometri growth is negative. The results of the protein content of fiddler (Uca spp) that there are two types that are not found that the protein content of the species Uca crassipes and Uca Dussumeri. The highest content of protein obtained from species of crab Uca arcuata by 20,05 %. In addition to the content uca Vocans obtained 9,84 % ; types uca Tetragonon obtained the protein content of 8,87 % and the type uca Rosea obtained by 2,87 % protein content. Habitat for fiddler crabs (Uca spp) in the area KKMB 9 Ha is salinity with a value range of 26,77+0,3ppt ; DO with a value range of 4,125+0,285 ppm ; pH with a value range of 7,5+0,06 ; temperature with a value range of 28 , 23 +0.290 C ; TDS with a value of 20.94 +0.22 ppm range . Habitat for fiddler crabs ( Uca spp ) in the area KKMB 13 Ha with a value range of salinity 27.25 +0.1 ppt ; DO with a value range of 4.33 +0.22 ppm ; pH value range of 7.5 +0 , 06 ; temperature with a value range of 28,65+0,14 C ; TDS with a value rangee of 21,285+0,075ppm.Keywords : Protein , Growth , Community , Fiddler (Uca spp) , KKMB Tarakan0